Prethrombotic Disorders in Thrombosis and Stroke - J Gordon Millichap (Pediatric Neurology Briefs)
The frequency of inherited and acquired prethrombotic disorders in 30 consecutive children with arterial ischemic stroke (AIS) and 10 with sinovenous thrombosis (SVT) was determined at the Hopital de Pediatria, Buenos Aires, Argentina.